use the factor theorem to determine whether g(x) is a factor of p(x) in each of the following cases:
(i) p(x)=x^3+3x^2+3x+1,g(x)=x+1
Answers
Answered by
1
If g(x) is a factor, then what happens if g(x) is zero?
p(x) will have 0 as a factor: p(x) becomes zero.
So we only have to make g(x) zero, then find if p(x) is also zero.
If p(x) doesn't have g(x) as a factor, p(x) won't become zero.
The required solution of g(x)=0 is x=-1.
Now we may apply the solution to p(x).
→ p(-1)=-1+3-3+1
→ p(-1)=0
Now g(x) is a factor of p(x), hence shown.
Answered by
2
Answer:
g(x) is not a factor of p(x).
Step-by-step explanation:
p(x)=x³+x²+3x+1
g(x)=>x+1=0
=>x=-1
p(-1)=> (-1)³+(-1)²+3(-1)+1=0
=>(-1)+1+(-3)+1=0
=>-2≠0
∴g(x) is not a factor of p(x).
Similar questions